Aerosol pollution, including eroded soils, intensifies cloud growth, precipitation, and soil erosion: A review. (10th July 2018) - Casazza, Marco; Lega, Massimiliano; Liu, Gengyuan; Ulgiati, Sergio; Endreny, Theodore A.
Abstract: The Earth's critical zone is vulnerable to atmospheric aerosol pollution due to aerosol impacts on cloud microphysics, precipitation characteristics, soil erosion, and the subsequent interactions of the soil-vegetation-atmosphere transfer of water, energy and aerosols. This review explains the individual and inter-connected processes of aerosol loading, cloud microphysics, precipitation characteristics, and soil erosion. A by-product of soil erosion is the generation of additional atmospheric aerosols, as well as the enhancement of surface erosion due to increased runoff. The literature includes empirical and theoretical studies within and across these domains. Case studies from China and Italy are provided to illustrate the key concepts connecting this system. The knowledge of the multiscale-impacts of aerosol pollution enables actions toward cleaner production processes to reduce aerosol pollution as well as forest and vegetation management to reduce soil erosion vulnerability. This review provides our community new insights on how to assess and manage earth's critical zone and our energy, food, water, and human resources.